Assessment of Brown top Millet Productivity and Fertility Status of Soil Grown as Intercropping with Different Legumes in Northern Transitional Zone of Karnataka - H. P., Darshan; Mansur, Chidanad P.; Shivamurthy, D.; Chaudhari, V. M. (International Journal of Economic Plants, 2025)
A field experiment was conducted during kharif season (June to October, 2021) at Main Agricultural Research Station, UAS, Dharwad, Karnataka, India to study the productivity and fertility status of soil as intercropping browntop millet with legumes. The experiment was laid out in randomized complete block design with thirteen treatments with three replications. Among thirteen treatments the browntop millet was intercropped with different legumes viz., groundnut, soybean, green gram and black gram in 4:2 and 2:1 row ratio and remaining treatments were individual sole crops. Among the different cropping systems, sole browntop millet was observed significantly higher grain and straw yield (973.61 and 2340.80 kg ha-1, respectively), but among the intercropping systems the 4:2 row proportion of browntop millet + groundnut was recorded higher grain yield (674.31 kg ha-1) and straw yield (1580.30 kg ha-1). There was no significant differences were seen between the different treatments in case of harvest index, but smong the different cropping system sole browntop millet was recorded numerically higher harvest index (32.81) and among the different intercropping system browntop millet+black gram with 2:1 row ratio was recorded numerically higher value (31.00). Among the different intercropping system browntop millet+black gram at 2:1 row ratio was recorded numerically higher available N (218.16 kg ha-1), P2O5 (28.37 kg ha-1) and K2O (271.57 kg ha-1) in the soil after crop harvest.